2004
DOI: 10.1083/jcb.200310059
|View full text |Cite
|
Sign up to set email alerts
|

Greatwall kinase

Abstract: Mutations in the Drosophila gene greatwall cause improper chromosome condensation and delay cell cycle progression in larval neuroblasts. Chromosomes are highly undercondensed, particularly in the euchromatin, but nevertheless contain phosphorylated histone H3, condensin, and topoisomerase II. Cells take much longer to transit the period of chromosome condensation from late G2 through nuclear envelope breakdown. Mutant cells are also subsequently delayed at metaphase, due to spindle checkpoint activity. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 30 publications
(33 reference statements)
5
97
1
1
Order By: Relevance
“…Data from a screen for gain-of-function mutants suggested that gwl is involved in motor axon guidance and synaptogenesis in larvae (29). More recently, gwl loss-offunction mutations that result in mitotic delay in larval neuroblasts and defective condensation of chromosomes in Drosophila cell cultures have been described (30). Embryos injected with gwl dsRNA lack some commissures, have breaks in the longitudinal connectives, and lack some segmental nerves ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data from a screen for gain-of-function mutants suggested that gwl is involved in motor axon guidance and synaptogenesis in larvae (29). More recently, gwl loss-offunction mutations that result in mitotic delay in larval neuroblasts and defective condensation of chromosomes in Drosophila cell cultures have been described (30). Embryos injected with gwl dsRNA lack some commissures, have breaks in the longitudinal connectives, and lack some segmental nerves ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a novel mitotic kinase important for proper timing of G2 -M transitions called Greatwall (GW) was discovered in Drosophila [46]. Subsequent work with Xenopus egg extracts revealed that GW is required for both establishment and maintenance of M phase [47,48].…”
Section: Cdk1-counteracting Phosphatases and Greatwallmentioning
confidence: 99%
“…It has been reported that both human and Drosophila Gwl localized in the nucleus during interphase, [17][18][19] whereas in Xenopus oocytes Gwl appeared predominantly cytoplasmic. 8 To investigate the subcellular localization of Gwl in Xenopus cells, we tagged the WT or G41S Gwl with DsRed, and expressed the recombinant proteins in Xenopus S3 cells harboring stable expression of GFP-a-tubulin.…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celmentioning
confidence: 99%